2019
DOI: 10.1515/zna-2019-0135
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Small Organic Molecules on Ti2+-Rich TiO2 Surfaces: Deoxygenation vs. C–C Coupling

Abstract: Rutile TiO2 is an important model system for understanding the adsorption and conversion of molecules on transition metal oxide catalysts. In the last decades, point defects, such as oxygen vacancies and Ti3+ interstitials, exhibited an important influence on the reaction of oxygen and oxygen-containing molecules on titania surfaces. In brief, partially reduced TiO2 containing a significant amount of Ti3+ is often more active for the conversion of such molecules. In this study, we investigate an even higher re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 68 publications
1
14
2
Order By: Relevance
“…7,21 Besides, one important difference between amines and alcohols appears to be regarding the adsorption in defect sites. While methanol, which is likely present as dissociated methoxy-fragments, desorbs under C−O dissociation forming methane above 500 K, 15,17,19,22 no such reactions were observed for either methylamine in this study or other amines in the report of Farfan-Arribas and Madix. 4 Hence, no doping of TiO 2 with atomic nitrogen leading to titanium oxonitrides (TiO x N y ) was observed within this work either.…”
Section: Introductioncontrasting
confidence: 57%
See 1 more Smart Citation
“…7,21 Besides, one important difference between amines and alcohols appears to be regarding the adsorption in defect sites. While methanol, which is likely present as dissociated methoxy-fragments, desorbs under C−O dissociation forming methane above 500 K, 15,17,19,22 no such reactions were observed for either methylamine in this study or other amines in the report of Farfan-Arribas and Madix. 4 Hence, no doping of TiO 2 with atomic nitrogen leading to titanium oxonitrides (TiO x N y ) was observed within this work either.…”
Section: Introductioncontrasting
confidence: 57%
“…In the last decades, the impact of (sub-)­surface defects such as oxygen vacancies or interstitial Ti 3+ sites has been recognized to be particularly relevant for the adsorption and reaction of small (organic) molecules on TiO 2 . In the case of ammonia, there are controversial findings. Due to the electronic charge that is supplied by the point defects, the acidity of the Ti 5c sites is decreased, and indeed, a shift of the desorption energy toward lower values was found. , In some reports, a decrease of the coverage is attributed to partial blocking of Ti 5c sites in the case of adsorption at oxygen vacancies. ,, However, other authors found that oxygen vacancies are not preferred adsorption sites for NH 3 molecules on rutile TiO 2 (110) either by hydroxylation of the vacancies or STM analysis. , Besides, one important difference between amines and alcohols appears to be regarding the adsorption in defect sites.…”
Section: Introductionmentioning
confidence: 99%
“…60 Analogously, Ti 3+ sites are expected to facilitate the C-O dissociation, suiting the trend for the thermal deoxygenation reaction forming methane. 15,17 One should note that Ti 3+ appears involved in almost all steps of the ethene formation starting from methanol (O-H dissociation, C-H dissociation, C-O dissociation). Therefore, the ethene yield is likely amplified not in a linear way but drastically more.…”
Section: Methanol Photo-oxidation On Rutile Tio 2 and Tungsten Oxide Clustersmentioning
confidence: 99%
“…11,12 By now, defects such as oxygen vacancies, Ti 3+ interstitials and other reduced sites are recognized to be an essential key to increase and further control the reactivity in thermal reactions towards oxygen and oxygen-containing molecules. [13][14][15][16][17][18][19][20] Their role in photochemical reactions, however, has not been studied so intensively in comparison. 4,5,[21][22][23] Therefore, we first focus on the methanol photochemistry on a rutile TiO 2 (110) surface as a function of the Ti 3+ content.…”
Section: Introductionmentioning
confidence: 99%
“…In this process, Ti 3+ from the bulk may serve as oxygen acceptors and may react with the leftover oxygen to form TiO x islands. 30,32,50,51 Besides the involvement of methoxy-intermediates adsorbed at the metal sites, it is challenging to derive more elementary reaction steps from our data. However, it is striking that the condensation yield is approximately equal for 3.5 and 7 WO 3 nm À2 .…”
Section: Trends In Product Distributions: Population Of Deoxygenation Partial Oxidation and Condensation Routesmentioning
confidence: 99%